Analisis Potensi Sertifikasi Halal Lewat Kesiapan Pelaku Usaha Mikro dan Kecil Produk Unggulan Makanan dan Minuman di Madura - Ahmad Makhtum; Muhammad Ersya Faraby (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2024)
Halal certification is an important part of creating an ecosystem for the halal product industry. The existence of halal certification will be an indicator of guaranteeing the availability of halal products for the community, as in Law No. 33 of 2014 concerning halal product guarantees. Therefore, product design for the implementation of halal product policies is an important part of building a halal product ecosystem, especially given the readiness of business actors. If the readiness of business actors, whose number is dominant in this case, is MSEs, then the process of implementing halal certification can be properly mapped and will become an important part of local design to create a halal product ecosystem to guarantee halal products. This research uses a qualitative method for explore readiness aspect for MSE’s in Pamekasan and Sampang districts, which are regencies in Madura, with Islamic nuances in everyday life. Some MSEs are ready to face the halal certification policy on the basis of business development and sustainability aspects.